1991
DOI: 10.1099/00207713-41-4-548
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Differentiation of Bifidobacteria of Human and Animal Origins

Abstract: The phenotypes of 153 strains belonging or related to the genus Bijidobacterium were studied. These organisms included 38 collection strains and 115 wild strains (41 strains of human origin, 56 strains of animal origin, and 18 strains obtained from rivers or sewage). Our phenotypic analysis revealed seven main groups that were subdivided into 20 subgroups. Seven subgroups contained no type or collection strain. Among the human strains, the type strains of BiJidobacterium pseudocatenulatum and B . catenulatum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 15 publications
2
50
0
2
Order By: Relevance
“…Because bifidobacteria were detected occasionally and in low counts in examined fish intestinal samples and species identified are considered as of human, animal or honeybee origin, we suppose that bifidobacteria were present only as environmental contamination from the water where fish stayed. Our conclusion is supported also by findings of Gavini et al (1991) who reported that Bifidobacterium species may be present in sewage or river water. They identified the isolates by API system and clustered by numerical analysis into groups with human, dog, pig, ruminant or rat bifidobacteria.…”
Section: Discussionsupporting
confidence: 81%
“…Because bifidobacteria were detected occasionally and in low counts in examined fish intestinal samples and species identified are considered as of human, animal or honeybee origin, we suppose that bifidobacteria were present only as environmental contamination from the water where fish stayed. Our conclusion is supported also by findings of Gavini et al (1991) who reported that Bifidobacterium species may be present in sewage or river water. They identified the isolates by API system and clustered by numerical analysis into groups with human, dog, pig, ruminant or rat bifidobacteria.…”
Section: Discussionsupporting
confidence: 81%
“…+, Positive; 2, negative; V, variable; ND, not determined. (Scardovi, 1986;Gavini et al, 1991;Crociani et al, 1996;Jian & Dong, 2002 …”
mentioning
confidence: 99%
“…(i) Cluster I. It was interesting that one of the strains (CUETM 89-271) isolated from child feces was also studied by Gavini et al (10) and clustered in their group VIIa but was not assigned to any known species. In this study, strain DSM 20097 (= C10-45) was unclustered in cluster I.…”
Section: (20)mentioning
confidence: 99%